Spending effects of child-related fiscal transfers - Olga Goldfayn-Frank; Vivien Lewis; Nils Wehrhöfer (Deutsche Bundesbank, 2022)
As part of Germany's fiscal response to the Covid-19 pandemic, parents received three payments totalling e450 per child. Randomization in the payment dates and daily scanner data allow us to identify the effects of these transfers on household spending. We find a significant but small spending effect of the first transfer, with an estimated marginal propensity to consume of about 12%. The effect is higher for low-income and liquidity-constrained households, and in areas with lower infection rates. The second and third payment failed to increase spending. Our results indicate that the child bonus was redistributive rather than stimulative.
Keywords: D12; E21; E62; H24; H31; 330; child bonus; Covid-19; fiscal stimulus; household spending; marginal propensity to consume; pandemic; transfer